Critical Race Theory and Copyright in American Dance - Picart, Caroline Joan S. author. aut Link
XII, 243 p. 6 illus.
Keywords: The effort to win federal protection for dance in the United States was a racialized and gendered contest. Picart traces the evolution of choreographic works from being federally non-copyrightable to becoming a category potentially copyrightable under the 1976 Copyright Act, specifically examining Loíe Fuller, George Balanchine, and Martha Graham.